The value of “diaphragmatic relaxing incision” for the durability of the crural repair in patients with paraesophageal hernia: a double blind randomized clinical trial - Tsoposidis, A.; Thorell, A.; Axelsson, H.; Reuterwall Hansson, M.; Lundell, L.; Wallenius, V.; Kostic, S.; Håkanson, B. (Frontiers in Surgery, 2023)
Background Surgical repair of paraesophageal hernias (PEHs) is burdened with high recurrence rates, and hitherto various techniques explored to enforce the traditional crural repair have not been successful. The hiatal reconstruction in PEH is exposed to significant tension, which may be minimized by adding a diaphragmatic relaxing incision to enhance the durability of the crural repair. Patients and methods All individuals undergoing elective laparoscopic repair of a large PEH, irrespective of age, were considered eligible. PEHs were classified into types II–IV. The preoperative work-up program included multidetector computed tomography and symptom assessment questionnaires, which will be repeated during the postoperative follow-up. Patients were randomly divided into a control group with crural repair alone and an intervention group with the addition of a left-sided diaphragmatic relaxing incision at the edge of the upper pole of the spleen. The diaphragmatic defect was then covered by a synthetic mesh. Results The primary endpoint of this trial was the rate of anatomical PEH recurrence at 1 year. Secondary endpoints included symptomatic gastroesophageal reflux disease, dysphagia, odynophagia, gas bloat, regurgitation, chest pain, abdominal pain, nausea, vomiting, postprandial pain, cardiovascular and pulmonary symptoms, and patient satisfaction in the immediate postoperative course (3 months) and at 1 year. Postoperative complications, morbidity, and disease burden were recorded for each patient. This was a double-blind study, meaning that the operation report was filed in a locked archive to keep the patient, staff, and clinical assessors blinded to the study group allocation. Blinding must not be broken during the follow-up unless required by any emergencies in the clinical management of the patient. Likewise, the patients must not be informed about the details of the operation. Trial Registration ClinicalTrials.gov, identification number NCT04179578.